A multiparameter implantable microstimulator SOC. - Chua-Chin Wang (IEEE Transactions on VLSI systems)
Various implantable microstimulators have been proposed for clinical applications in recent years. Most of the no-battery implanted devices can be powered by a transcutaneous magnetic coupling, which basically utilizes an external transmitter coil to power and communicate with the implanted device. Small chip area and low power consumption are the keys of the implanted device. Therefore, we propose a C-less (no capacitor) area-saving ASK demodulator in this work to get rid of those large discrete capacitors required for low-frequency ASK demodulation. Additionally, a power regulator supplying a stable VDD_OUT is also built in to resolve the unstable supply voltage problem resulted from the inductive link. Besides, a multiparameter control protocol which has an area advantage over microcontroller-based solutions is also proposed for various pain treatments of muscles and stimulating applications.